2022
DOI: 10.1186/s12920-022-01413-7
|View full text |Cite
|
Sign up to set email alerts
|

Construction and experimental validation of an acetylation-related gene signature to evaluate the recurrence and immunotherapeutic response in early-stage lung adenocarcinoma

Abstract: Background Acetylation is a reversible epigenetic process, playing an important role in the initiation and progression of malignant tumors. However, the prognosis value of acetylation-related genes in the early-stage lung adenocarcinoma (LUAD) remains obscure. Materials and methods The acetylation-related genes were collected and clustered based on transcriptome sequencing of the patients with early-stage LUAD from the Cancer Genome Atlas. The geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Recently, the establishment of diagnosis or prognosis models from the particular aspect of biological processes, such as ferroptosis, 45,46 necrosis, 47 lipid metabolism, 48,49 and acetylation, 50 and the tumor immune microenvironment, 51,52 has attracted increasing interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the establishment of diagnosis or prognosis models from the particular aspect of biological processes, such as ferroptosis, 45,46 necrosis, 47 lipid metabolism, 48,49 and acetylation, 50 and the tumor immune microenvironment, 51,52 has attracted increasing interest.…”
Section: Discussionmentioning
confidence: 99%
“…With the rise and development of big‐data analysis and high‐throughput sequencing, an increasing number of predictive models based on molecular expression levels have been proposed, helping to guide personalized treatment and reduce the costs of treatment. Recently, the establishment of diagnosis or prognosis models from the particular aspect of biological processes, such as ferroptosis, 45 , 46 necrosis, 47 lipid metabolism, 48 , 49 and acetylation, 50 and the tumor immune microenvironment, 51 , 52 has attracted increasing interest. Similar to these studies, the established model in our study was based on platelets and M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that the expression levels of RBBP7 in NSCLC are higher than those in normal lung tissues, and this elevated expression is associated with distant metastasis, poor prognosis and tumor immune response in NSCLC, serving as a predictor for the recurrence of early-stage NSCLC (88)(89)(90).…”
Section: Respiratory Systemmentioning
confidence: 99%
“…Some scholars collected acetylation-related genes in the transcriptome of early LUAD patients in the TCGA database to try to identify the important biomarkers of early LUAD recurrence through differential analysis and protein–protein interaction network construction. Finally, they concluded that the two gene signatures of RBBP7 and YEATS2 can be used to predict the recurrence-free survival of early LUAD [ 56 ].…”
Section: The Applications Of Ai and ML In Lung Cancer Immunotherapy P...mentioning
confidence: 99%